Frequency of latent tuberculosis in patients receiving Anti-TNF-Alpha therapy - Coşkunol, İpek; Turan, Onur; Baysak, Ayşegül; Solmaz, Dilek; Can, Gerçek (Makerere University, Medical School, 2023)
Setting-Objective: In this study, it was aimed to reveal the incidence of tuberculosis development in patients receiving tumor necrosis factor-alpha (TNF-?) blocker therapy, despite tuberculosis chemoprophylaxis. Design: 520 patients who were receiving anti TNF-? treatment in the last 3 years were evaluated retrospectively. Radiological imaging tuberculin skin test (TST), history of tuberculosis, BCG vaccine, chemoprophylaxis administration, used anti TNF-? drugs were recorded. Results: There were 265(51.0%) of the patients with ankylosing spondylitis (AS), 175(33.7%) with rheumatoid arthritis, 35(6.7%) with Crohn's, 10(1.9%) with ulcerative colitis (UC), 21(4.0%) with psoriatic arthritis, 14(2.7%) with psoriasis vulgaris. In total, 455 (79.6%) patients were given INH prophylaxis. Active tuberculosis development was observed in five patients (4: pulmonary,1: extrapulmonary; 3: UC, 2:AS) who all received anti TNF-? treatment (0.96%), infliximab. Three patients had tuberculosis disease in the 6th month, and the other 2 patients in the 5th and 24th month of their anti TNF-? treatments, and two had 9-month, and 1 had 6-month chemoprophylaxis history. Conclusion: The incidence of tuberculosis development in patients treated with anti TNF-? was found to be higher than the general population. In our country, where tuberculosis is still prevalent, patients receiving Anti TNF-? treatment (especially in-fliximab) should be carefully questioned and examined about tuberculosis.
Keywords: Anti-TNF-Alpha; Tuberculin Skin Test; Tuberculosis